Efektivitas Implementasi Monitoring Intensif Pemanfaatan Antrean Online melalui Mobile JKN di Fasilitas Kesehatan Rujukan Tingkat Lanjutan (FKRTL) Champion Kantor Cabang Bulukumba Tahun 2022. - Muhayyina Wahidah; Andi Rismaniswati Syaiful; Rini Oktaviani Najib; ihwan Prasetiya; Andi Syamsul Bakhri; Andi Rifka Yuliana Sari; Lily Alfy Sahraini; Muhammad Fiqri Adim; Muhammad Rezki; I Gede Bayu Edwin Jenuar (BPJS Kesehatan, 2023)
This study aims to assess the effectiveness of the implementation of intensive monitoring of the achievements of online queuing system utilization through Mobile JKN for FKRTL Champion in 2022. The method used is descriptive quantitative by comparing data on online queue utilization, quality rate (QR), and the average total service time for outpatient visits through Mobile JKN before and after the implementation of monitoring and piloting of 3 (three) FKRTL Champions in Bulukumba District, Bantaeng Regency, and Jeneponto Regency in 2022 which were chosen to represent each type and class of FKRTL. The results of the study found that the implementation of intensive monitoring and the piloting of 3 FKRTL Champions which had been carried out since December 2022 had effectively increased the achievement of using online queues through Mobile JKN compared to other collaborative FKRTLs. Apart from that, intensive monitoring and the piloting of FKRTL Champion can also increase the Quality Rate with an average achievement above 80%, and the use of online queues through Mobile JKN effectively shows the efficiency of the average service time at FKRTL outpatient services at FKRTL Champion